1985
DOI: 10.1007/bf00916279
|View full text |Cite
|
Sign up to set email alerts
|

Human vascular smooth muscle cells and endothelial cells lack catalase activity and are susceptible to hydrogen peroxide

Abstract: 51Cr release as lytic and cell detachment as nonlytic injury were employed to estimate neutrophil-mediated injury of cultured human vascular smooth muscle cells and endothelial cells. The reagents hydrogen peroxide or hypoxanthine-xanthine oxidase produced dose-dependent killing and nonlytic cell detachment, which were specifically inhibited by catalase but not by superoxide dismutase. The concentration of hydrogen peroxide or xanthine oxidase to induce cell detachment was less than lytic dose, suggesting that… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
39
0

Year Published

1988
1988
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 84 publications
(40 citation statements)
references
References 33 publications
1
39
0
Order By: Relevance
“…Our findings agree with previous data that catalase was unchanged in the aortas of Gpx1-deficient mice (33). Although catalase overexpression has been shown to limit lesion formation in apolipoprotein E-deficient mice (39), its role as a major player in the protection against atherosclerosis is questionable because catalase enzymatic activity is known to be particularly low in the vasculature (44). The expression profiles of other enzymes implicated in cellular antioxidant defense were also investigated in this study.…”
Section: Lack Of Gpx1 Does Not Increase Murine Atherosclerosissupporting
confidence: 82%
“…Our findings agree with previous data that catalase was unchanged in the aortas of Gpx1-deficient mice (33). Although catalase overexpression has been shown to limit lesion formation in apolipoprotein E-deficient mice (39), its role as a major player in the protection against atherosclerosis is questionable because catalase enzymatic activity is known to be particularly low in the vasculature (44). The expression profiles of other enzymes implicated in cellular antioxidant defense were also investigated in this study.…”
Section: Lack Of Gpx1 Does Not Increase Murine Atherosclerosissupporting
confidence: 82%
“…Among the oxygen radicals. HP may be responsible for the killing of cultured endothelial eells [20], fibroblasts [21] and vascular smooth muscle cells [22]. HP can activate latent collagenase, and inhibit collagen gelation and proteoglycan synthesis by cartilage [23 25], It has been shown that latent collagenase is activated by HP-related products [26].…”
Section: [Ntroductionmentioning
confidence: 99%
“…Studies that used the manipulation of genes for antioxidant enzymes 11,12 to test the effects of oxidants on cells also corroborate the assumption that intracellular oxidative stress might play an important role in the transduction of oxidative stress from external sources to intracellular sites. Previously, Shingu et al 13 showed that endothelial cells and smooth muscle cells have very low levels of catalase activity and therefore are more susceptible to damage by H 2 O 2 . Several studies had attempted to overexpress catalase enzyme in various cell types and looked for the effect of this enzyme in preventing oxidation-related damage.…”
mentioning
confidence: 99%